Dynamic Update Anaphora Logic: A Simple Analysis of Complex Anaphora. (29th January 2018) - Keshet, Ezra
Abstract: An antecedent relationship may hold between an indefinite and a pronoun across non-quantified sentences ('Jane bought a book. She read it immediately.'), from the restrictor to the nuclear scope of a single quantified sentence ('Every woman who bought a book read it immediately.'; Geach 1962 ), and even across two quantified sentences ('Every woman bought a book. Most read it immediately.'; Sells 1985 ). First-generation dynamic semantic systems (Kamp 1981 ; Heim 1983 ; Groenendijk & Stokhof 1991 ) cannot handle anaphora across quantified sentences, but do handle the first two cases above quite elegantly: anaphora within a single quantified sentence (i.e. donkey anaphora) is a simple extension of anaphora across non-quantified sentences. Dynamic Plural Logic (van den Berg 1996 ) expands empirical coverage to anaphora across two quantified sentences (i.e. quantificational subordination) by generalising all three cases above to this worst case. This paper presents Dynamic Update Anaphora Logic, an alternative extended logic that introduces variables to store full dynamic clause meanings and compound variable terms to construct sets of individuals. Clause meanings may be retrieved later to handle donkey anaphora and quantificational subordination as straightforward extensions to non-quantified cross-sentential anaphora. This new system also handles paycheck pronouns (Karttunen 1969b ), an empirical deficit of Dynamic Plural Logic.